Effect of Gliclazide or Gliclazide plus Metformin Combination on Glycemic Control in Patients with T2DM in India: A Real-World, Retrospective, Longitudinal, Observational Study from Electronic Medical Records - Nareen Krishna Polavarapu; Ravindra Kale; Bipin Sethi; R. K. Sahay; Uday Phadke; Santosh Ramakrishnan; Amey Mane; Suyog Mehta; Snehal Shah (Adis, Springer Healthcare, 2020)
Abstract Background The efficacy of gliclazide has been reported in clinical trials in India. However, real-world data on the effectiveness of gliclazide in India is unavailable. Objective To provide real-world evidence regarding the effectiveness of gliclazide or gliclazide + metformin fixed-dose combination or separate medications, used either as monotherapy or as the latest add-on to other antihyperglycemic agents in reducing glycated hemoglobin (HbA1c) levels in Indian patients with type 2 diabetes mellitus (T2DM). Methods Electronic medical record data of adult patients who were diagnosed with T2DM who were newly initiated on or had been prescribed gliclazide or gliclazide + metformin combination for < 30 days as monotherapy or as add-on therapy to other antihyperglycemic agents, and had HbA1c ≥ 6.5% were retrospectively analyzed. Mean change in HbA1c from baseline was the primary endpoint. Secondary endpoints were assessment of dosages and formulations of gliclazide or gliclazide + metformin prescribed in the HbA1c spectrum and antihyperglycemic agents to which gliclazide or gliclazide + metformin was added as an adjunct. Readings were obtained before initiating gliclazide or gliclazide + metformin and after at least 90 days of treatment with gliclazide or gliclazide + metformin. Results Included patients (n = 498) were categorized into gliclazide only (n = 66), gliclazide + metformin only (n = 179), gliclazide add-on (n = 169), and gliclazide + metformin add-on (n = 84) groups. Mean (95% confidence interval [CI]) change in HbA1c among patients with baseline HbA1c > 7% was − 0.8% (− 1.26, − 0.34) in gliclazide only group; − 1.6% (− 1.89, − 1.31; p < 0.001) in gliclazide + metformin group; − 1.2% (− 1.50, − 0.90; p < 0.001) in add-on gliclazide group; and − 1.4% (− 1.75, − 1.05; p < 0.001) in add-on gliclazide + metformin group. Gliclazide once daily was the most prescribed regimen in the gliclazide only group (72.7%), with 60 mg being the most prescribed modified-release dose (62.5%). Gliclazide + metformin twice daily was the most prescribed regimen in the gliclazide + metformin group (69.3%) with 80 mg + 500 mg being the most prescribed immediate-release dose (62.9%). Gliclazide and gliclazide + metformin were most added as an adjunct to existing prescriptions of biguanides (83.4%) or insulin (64.3%), respectively. Conclusion Gliclazide or gliclazide + metformin prescribed as mono- or add-on therapy during routine clinical practice effectively reduced HbA1c in Indian patients with T2DM, thus validating the use of gliclazide and gliclazide + metformin for managing T2DM in India.